2017
DOI: 10.5194/bg-14-5647-2017
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of chlorophyll distribution in the Gulf of Mexico: bio-optical data from profiling floats

Abstract: Abstract. Chlorophyll concentration is a key oceanic biogeochemical variable. In the Gulf of Mexico (GOM), its distribution, which is mainly obtained from satellite surface observations and scarce in situ experiments, is still poorly understood. In 2011-2012, eight profiling floats equipped with biogeochemical sensors were deployed for the first time in the GOM and generated an unprecedented dataset that significantly increased the number of chlorophyll vertical distribution measurements in the region. The ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 89 publications
10
46
0
1
Order By: Relevance
“…Throughout their westward trajectory, they sink underlying isotherms, as is evinced by the shape of the depth of the 6°C isotherm (T6) during the three XIXIMI cruises (Figures 2d-2f). Following the criteria described by Pasqueron de Fommervault et al (2017), the vertical displacement of the T6 isotherm is used as a proxy for mesoscale feature detection, since it is approximately located at the base of the LC and LCEs and at 400-to 600-m depth in cyclonic eddies. Notably, those stations under the anticyclonic influence of the LC and their LCEs, such as station B12 and northeast locations during the three cruises, depict a deeper T6 (>820 m).…”
Section: Mesoscale Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout their westward trajectory, they sink underlying isotherms, as is evinced by the shape of the depth of the 6°C isotherm (T6) during the three XIXIMI cruises (Figures 2d-2f). Following the criteria described by Pasqueron de Fommervault et al (2017), the vertical displacement of the T6 isotherm is used as a proxy for mesoscale feature detection, since it is approximately located at the base of the LC and LCEs and at 400-to 600-m depth in cyclonic eddies. Notably, those stations under the anticyclonic influence of the LC and their LCEs, such as station B12 and northeast locations during the three cruises, depict a deeper T6 (>820 m).…”
Section: Mesoscale Dynamicsmentioning
confidence: 99%
“…Temporal dynamics of nitracline depth, MLD, light availability, and trophic interactions (as control of autotrophic abundances and cell sizes) have been suggested as the influential factors for the pico-phytoplankton seasonal variability observed in these subtropical regions (Pasulka et al, 2013). Nonetheless, changes in phytoplankton biomass and particularly picoplankton variability in the southern GoM region may be additionally attributable to other mechanisms, such as the dynamics of mesoscale structures, which are superimposed to the seasonal processes throughout the year (Pasqueron de Fommervault et al, 2017).…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Despite the strong scattering, in situ data shows the presence of a DCM from spring to autumn(Pasqueron de Fommervault et al, 2017) that is also reproduced by GOLFO12-PISCES. Conversely, in winter, model [CHL] values are more homogenized near the surface, in agreement with in situ data(Pasqueron de Fommervault et al, 2017). The DCM is well reproduced in GOLFO12-PISCES, although the [CHL] DCM is 13% higher in observations(Figure 3).…”
mentioning
confidence: 99%
“…Previous satellite-based studies have revealed a clear seasonal cycle in surface chlorophyll with highest concentrations in winter and lowest in summer (Martínez-López and Zavala-Hidalgo, 2009;Muller-Karger et al, 1991, 2015. Thanks to advances in autonomous profiling technology, recent studies based on simultaneous measurements of subsurface chlorophyll and backscatter have demonstrated that the seasonal variability of surface chlorophyll might be a result of the vertical redistribution of subsurface chlorophyll and/or physiological response to solar radiation of phytoplankton (Fommervault et al, 2017;Green et al, 2014).…”
Section: Study Regionmentioning
confidence: 99%
“…nutrients, light, and temperature) (Cullen, 2015;Fennel and Boss, 2003;Geider, 1987). Thus, changes in chlorophyll may result from physiologically induced modifications of the chlorophyll-to-phytoplankton ratio rather than actual changes of phytoplankton biomass (Fommervault et al, 2017;Mignot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%